Examining the Relationship Between Whistleblowing Policies and Internal Audit Effectiveness in Corporations (gjstudies, 2019)
The contemporary corporate landscape has witnessed increasing attention to internal controlmechanisms and ethical compliance frameworks, particularly in the aftermath of significantcorporate scandals and regulatory reforms. Within this context, whistleblowing policies andinternal audit functions represent two critical components of organizational governance thathave traditionally been examined as separate entities. This research bridges this conceptualgap by investigating the intricate relationship between whistleblowing policy frameworks andinternal audit effectiveness through an innovative methodological approach that combinescomputational analysis with traditional audit assessment techniques.